Ecosystems and Human Health A Critical Approach to Ecohealth Research and Practice - Dakubo, Crescentia Y. (Springer New York : Imprint: Springer, 2010)
Ecosystems and Human Health A Critical Approach to Ecohealth Research and Practice Crescentia Dakubo The magnitude of current epidemics, environmental disasters, and extreme weather events is proving that human health problems require more comprehensive solutions than conventional biomedical approaches can offer. At the intersection of the public and community health, global health, and environmental fields, Ecohealth advocates improved health outcomes through better ecosystems management. But even as the Ecohealth approach gains acceptance, literature on the subject is scarce. Ecosystems and Human Health introduces Ecohealth as an emerging field of study, traces its evolution, and explains its applications in cross-disciplinary and holistic programs. Its integrative approach not only focuses on managing the environment to improve health, but also analyzes underlying social and economic determinants of health to develop innovative, people-centered interventions. This unique text: • Expands on the theoretical systems that underlie Ecohealth. • Examines the relationships between human health and the biophysical, political, cultural, and socioeconomic environments. • Discusses the methodological issues and the participatory action research process associated with Ecohealth. • Provides detailed case studies illustrating the approach in developing and developed areas of the world. • Suggests applications of Ecohealth methods to influence public health policy. • Offers practical tools for readers designing and carrying out Ecohealth projects. • Proposes a critical approach to Ecohealth research and practice. Ecohealth holds vital keys to pressing global concerns, giving Ecosystems and Human Health a particular urgency for researchers, students, policymakers, and community and public health practitioners.